Boosting the mustard production technology through front line demonstrations in Pali district of Rajasthan (Journal of Oilseed Brassica, 2026)
Total 370 Frontline demonstrations (FLDs) at farmers field were laid out of Indian mustard (Brassica juncia L.) to demonstrate production potential and economic benefits of improved practices (IP) comprising high yielding new varieties namely NRCDR 2 and DRMRIJ 31 in Pali district of arid zone of Rajasthan state during Rabi seasons of 2012- 13 to 2015-16 in irrigated farming situations. The per cent increased yield under improved practices ranged 36.7 to 51.2 (NRCDR 2) and (DRMRIJ 31) in respective years. The average extension gap, technology gap and technology index were 5.3 qha-1, 4.4 qha-1 and 19.6 per cent, respectively in both varieties of Indian mustard. The improved practices gave higher benefit cost ratio ranging 2.6 to 3.4 with a mean of 3.0 compared to farmers’ practices (2.2). The productivity of Indian mustard per unit area could be increased by adopting feasible scientific and sustainable management practices with a suitable variety. Results revealed the worth of a new variety to convince the farming community about potentialities of improved production management technologies for further adoption could enhance the productivity and production of Indian mustard.